OPTIMASI WADUK REGULATING DAM DI KABUPATEN PRINGSEWU, PROVINSI LAMPUNG - Dharmawan Setioko; Gatot Eko Susilo; Ahmad Zakaria (Rekayasa : Jurnal Ilmiah Fakultas Teknik Universitas Lampung, 2015)
Argoguruh Weir is the biggest irrigation weir in Lampung Province. This hydraulic structure was developed in 1935, crossing Way Sekampung River and serving Sekampung Irrigation Area which is about 67,000 ha. This weir is supplied by water from Batutegi Dam and baseflow of the upper Way Sekampung basin. Excessive water in Argoguruh Weir is passing by and flowing to the sea. Due to this condition, the government plan to build a dam between Batutegi Dam and Argoguruh Weir. This research aims to carry out a simulation of water balance in the Regulating Dam in order to find the best operational pattern for the dam. The Objective function of the simulation is water ele- vation of reservoir with probability more than 80%. The constrain of the simulation is that water elevation of the reservoir has to be higher than the water elevation of reservoir dead storage that is +102.30 m. Discharge data used in the simulation is daily discharge data of Argoguruh Weir from the year 2005 to the year 2013. The simulation is operated in 15-days time basis. Results of the simulation indicate that the objective function of the simulation is found in elevation +116.07 m with probability of 80.09%. On that condition, water from the reservoir is utilised for PDAM Pringsewu water supply and for the water supply for 242.90 ha new irrigation area. The lowest water elevation in this condition is +111.86 m. This water elevation is much more higher than the one of reservoir dead storage.